The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/14651858.cd002783.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis for acute deep vein thrombosis

Abstract: A B S T R A C T BackgroundStandard treatment for deep vein thrombosis aims to reduce immediate complications. Use of thrombolysis or clot dissolving drugs could reduce the long-term complications of post-thrombotic syndrome (PTS) including pain, swelling, skin discolouration, or venous ulceration in the affected leg. This is the third update of a review first published in 2004. ObjectivesTo assess the effects of thrombolytic therapy and anticoagulation compared to anticoagulation alone for the management of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
156
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(166 citation statements)
references
References 54 publications
1
156
0
3
Order By: Relevance
“…Selection of patients must be guided by a multidisciplinary approach, with inputs from a vascular surgeon and interventional radiologist, and must consider patient preferences 2845464748…”
Section: How Is It Treated?mentioning
confidence: 99%
“…Selection of patients must be guided by a multidisciplinary approach, with inputs from a vascular surgeon and interventional radiologist, and must consider patient preferences 2845464748…”
Section: How Is It Treated?mentioning
confidence: 99%
“…In the pharmacomechanical-thrombolysis group, there were more early major bleeds than in the control group, but less major bleeding (1.7% of patients, with no fatal or intracranial bleeds) occurred in association with the procedure than in past studies of thrombolysis for deep-vein thrombosis. 3,7,18,3436 …”
Section: Discussionmentioning
confidence: 99%
“…5,6 Small randomized trials have suggested that active removal of acute thrombus may preserve venous function and prevent the post-thrombotic syndrome (the “open-vein hypothesis”). 3,7,8 …”
mentioning
confidence: 99%
“…PTS is thought to be caused by venous hypertension due to persistent venous obstruction/insufficiency after inflammatory destruction of venous valves following a DVT 9. A systemic review showed that systemic thrombolysis offers a significant advantage, reducing the incidence of PTS by one-third 10. This may be due to early recanalisation reducing the inflammatory destruction of valves following a DVT.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the dose reduction, evidence suggests that CDT is as effective as systemic thrombolysis in reducing the incidence of PTS 10. Current evidence on the use of CDT in pregnancy is limited but have demonstrated successful clot lysis with no complications to the fetus 16.…”
Section: Discussionmentioning
confidence: 99%